p53 protein in esophageal mucosa of individuals at high risk of squamous cell carcinoma of the esophagus - Fagundes, R. B.; Mello, C. R.; Tollens, P.; Pütten, A. C. K.; Wagner, M. B.; Moreira, L. F.; Barros, S. G. S. (Diseases of the esophagus, 2001)
Squamous cell carcinoma of the esophagus (SCCE) is diagnosed late and carries a poor prognosis. Biomarkers such as p53 protein expression may be present in the esophageal mucosa long before esophageal symptoms or lesions appear and may point toward early diagnosis. Asymptomatic subjects at high risk for SCEE (consumption of more than 80 g of ethanol and 10 cigarettes/day for at least 10 years) underwent upper gastrointestinal endoscopy with biopsies of the esophageal mucosa, and expression of p53 protein was compared with conventional histologic findings. In 182 subjects studid, p53 protein was expressed in a stepwise fashion according to the severity of the histologic findings: normal mucosa (12/103 or 11.7%), mild chronic esophagitis (6/43 or 14%), moderate chronic esophagitis (4/18 or 22.2%), severe chronic esophagitis (1/3 or 33.3%), low‐grade dysplasia (4/11 or 36.4%), high‐grade dysplasia (2/2 or 100%), and squamous cell carcinoma (2/2 or 100%) (P=0.00025). The odds ratio and confidence intervals were calculated by logistic regression, with multivariate adjustment for potentially confounding variables. The risk for p53 expression was twofold for moderate and severe chronic esophagitis and 10‐fold for dysplasia and cancer (P=0.001). p53 protein was expressed not only in cancerous lesions, high‐grade and low‐grade dysplasia, as expected, but also in mucosa considered normal or with chronic esophagitis using conventional histology. Smokers and alcohol drinkers with normal mucosa or chronic esophagitis that express p53 protein may represent an unrecognized subgroup of individuals that may benefit from surveillance. Follow‐up studies of these asymptomatic subjects and molecular analysis of the p53 gene are needed to clarify this point.